Current Account Dynamics : The Role of Real Shocks. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper demonstrates how a full-blown optimizing model of the dynamics of the current account can be reduced to a small-scale collection of reduced-form relations capable of implementing a rich set of macro-economic simulations. Emphasizing the role of shocks to productivity, labor employment, world rate of interest, and tax revenues the analysis can account for movements in trade imbalances, and the decline in private saving and investment observed recently in developed open economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet